Between Communication, Architecture and Art. Mosaic in Urban Space – the Work of Ignacy Bieniek - Groń Krzysztof Józef; Gawroński Sławomir; Szewczyk Marcin; Groń Kacper; Wybraniec Julia (Architecture, Civil Engineering, Environment)
The article refers to the functions that mosaics may perform in urban space. They are relics of ancient times, but they have found new enthusiasts in the latest century. Therefore, street mosaic is treated by the Authors as a part of architecture and communication medium. In Poland, mosaics frequently became a part of the socialist realism doctrine and were created within the context for propaganda purposes. The aim of this study is to present mosaic as a medium of communicative as well as artistic and urban character. Based on the historically and artistically researched mosaic by Bieniek, we can see the significance of artistic works, in the context of architecture but also sociology. The methods chosen to achieve this aim were desk research and a case study of work by Bieniek. The mosaic, which was destroyed, was a significant example of the use of this art form in public space. Analyzing mosaic we notice that introducing interaction with art makes the recipient get to know it more deeply, becoming its integral part. This identification allows us to arouse sentiment for the historical value of the work, which contributes to the cultivation of the culture surrounding us.